The emerging threat antifungal-resistant Candida tropicalis in humans, animals, and environment - Lima, Ricardo; Ribeiro, Felipe C.; Colombo, Arnaldo L.; de Almeida, Joăo N. (Frontiers in Fungal Biology, 2022)
Antifungal resistance in humans, animals, and the environment is an emerging problem. Among the different fungal species that can develop resistance, Candida tropicalis is ubiquitous and causes infections in animals and humans. In Asia and some Latin American countries, C. tropicalis is among the most common species related to candidemia, and mortality rates are usually above 40%. Fluconazole resistance is especially reported in Asian countries and clonal spread in humans and the environment has been investigated in some studies. In Brazil, high rates of azole resistance have been found in animals and the environment. Multidrug resistance is still rare, but recent reports of clinical multidrug-resistant isolates are worrisome. The molecular apparatus of antifungal resistance has been majorly investigated in clinical C. tropicalis isolates, revealing that this species can develop resistance through the conjunction of different adaptative mechanisms. In this review article, we summarize the main findings regarding antifungal resistance and Candida tropicalis through an “One Health” approach.